DISINFORMATION AND DIGITAL ELECTORAL CRIMES: CHALLENGES FOR DEMOCRACY - de Souza, Yasmin Gabriely Cardoso; Lima, Caroline de Oliveira; Santana, Jhonn Állex Moreira; Sousa, Jonas Antonio da Silva; Graciano, Marcos Vinícius Rodrigues; de Souza, Pedro Arthur Ferreira; Ferreira, Valdivino José; Sancho, Filipe Augusto Caetano (CIPEEX, 2025)
Contemporary politics faces profound transformations driven by technological advances, which generate both positive and negative effects. Among the main challenges are the spread of disinformation and the rise of digital electoral crimes, which threaten democratic integrity. This paper aims to examine the effects of disinformation and digital electoral crimes on democracy, focusing on the application of technologies such as artificial intelligence in political campaigns. This study was developed based on a methodological approach of bibliographical research and a review of Brazilian regulations, such as Law No. 9,504/1997 and TSE resolutions. The data obtained demonstrate that the application of technologies, such as artificial intelligence, in political campaigns has the potential to influence voters in a manipulative manner, requiring effective measures to combat fake news, especially in the Brazilian electoral context. For this to happen, it is necessary to strengthen political education, contributing to the formation of a critical and conscious society, capable of resisting misinformation and illicit practices. In this context, the responsible use of technology, combined with the dissemination of truthful information and the appreciation of ethics in politics, can strengthen democracy. Therefore, although the challenges are great, it is possible to move toward a more reliable and representative electoral system. A well-informed society is the foundation of a solid democracy, capable of protecting itself against abuse and manipulation, reaffirming the importance of education, ethics, and oversight in the current political landscape.